Models of indicator systems of construction contraction agreements - Sigitas Mitkus; Eva TrinkÅ«nienÄ— (Journal of Civil Engineering and Management, 2006)
A number of multicriteria decisions must be made during construction investment processes. A number of support systems for multicriteria tasks of construction investment processes are available. A part of them is reviewed in this article. Effectiveness of the construction investment process is greatly influenced by an appropriate formulation of a construction contraction agreement (CCA). In order to formulate the effective contraction agreements, multicriteria techniques for evaluating and comparing CCAs must be created. Besides technical, organisational and economic aspects of construction, legal aspects of a CCA must be also analysed in order to prepare such techniques. Therefore, legal decision making systems are also reviewed in the article. A conclusion can be made from the review that legal decision making systems for CCAs are not available currently. One of the main tasks in the creation of multicriteria support systems is the formation of a multicriteria indicator system. Three models of multicriteria indicator systems of CCAs are analysed in the article, and the best model for creating multicriteria evaluation technique is determined. On the basis of this model, significance of indicators should be determined and a multicriteria decision support system should be created in further research stages.